Impact of diastolic pulmonary gradient and pulmonary artery pulse index on outcomes in heart transplant patients—Results from the Eurotransplant database - Wagner, Tobias; Magnussen, Christina; Bernhardt, Alexander; Smits, Jacqueline M.; Steinbach, Katrin; Reichenspurner, Hermann; Kirchhof, Paulus; Grahn, Hanno (Frontiers in Cardiovascular Medicine, 2022)
Background Predicting complications associated with pulmonary hypertension (PH) after cardiac transplantation is an important factor when considering cardiac transplantation. The transpulmonary gradient (TPG) is recommended to quantify PH in transplant candidates. Nonetheless, PH remains a common driver of mortality. The diastolic pressure gradient (DPG) and pulmonary vascular resistance (PVR) can differentiate post- from combined pre- and post-capillary PH and may improve estimation of PH-associated risks. We used a large European cohort of transplant candidates to assess whether the pulmonary pulsatility index (PAPi), improves prediction of graft failure and mortality compared to DPG and PVR. Methods Out of all patients undergoing heart transplantation between 2009 and 2019 in Eurotransplant member states (n = 10,465), we analyzed the impact of PH (mPAP > 25 mmHg) and right heart catheter hemodynamic data on graft failure and mortality within 1–5 years. Results In 1,407 heart transplant patients with PH (79% male, median age 54 years, IQR 39–69 years), the median PVR was 2.5 WU (IQR 1.6 WU) with a median mPAP (pulmonary arterial pressure) of 32 mmHg (IQR 9 mmHg). Patients with low (< 3 mmHg) DPG had a better 5 year survival than those with higher DPG (log rank p = 0.023). TPG, mPAP, PAPi, and PVR did not improve prediction of survival. Low PAPi (OR = 2.24, p < 0.001) and high PVR (OR = 2.12, p = 0.005) were associated with graft failure. Conclusion PAPI and PVR are associated with graft failure in patients with PH undergoing cardiac transplantation. DPG is associated with survival in this cohort.